Pelatihan Model Asesmen Pengembangan Karakter Katekisan Bagi Pengajar Katekisasi di Gereja Masehi Injili di Timor (GMIT) - Sine, Junaity Soften; Sibulo, Deviana; Baun, Nofriana; Nomnafa, Fregianus; Lassa, Yenny (Edumedia Solution, 2022)
Catechesis in Gereja Masehi Injili di Timor (GMIT) is vital in building the faith of the church youth. The curriculum still needs to be fully developed. Therefore, the assessment only emphasizes the students’ cognitive aspect. In order to support and equip the teachers, community service was held. The purpose of the service was to give them chances to learn more about how to design a proper and holistic assessment in Catechesis. The activity was conducted in three phases: preparation, implementation, and evaluation. After the conference, the participants reflect on their experiences, obstacles, and ideal concept of the character assessment. Overall, they understood the importance of carefully thinking and designing the curriculum appropriately.